![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: 7(y+3)-2x+2)=14 4(y-2)+3(x-3)=2 by substitution method - increase by 7 the roots of the equation 3x^4+7x^3-15x^2+x-2=0 - 2+3=10 and 8+4=96 and 7+2=63 and 6+5=66 and 9+5= - 7(y+3)-2x+2)=14 4(y-2)+3(x-3)=2 by elimination method - 1 2 7 2 3 4 - 1+4+7+...+(3n-2 n(3 n-1)/2 mathematical induction - if x=√3+1/2 find the value of 4x^3+2x^2-8x+7 - 1+4+7+10+...+(3 n-2)=1/2 n(3n-1) - 1/6(4y+5)-2/3(2y+7)=3/2 - 3x+2/7+4(x+1)/5=2/3(2x+1) - 1 2 7 2 3 4 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.